Fungal infections of the central nervous system and paranasal sinuses in onco‐haematologic patients. Epidemiological study reporting the diagnostic‐therapeutic approach and outcome in 89 cases. Issue 3 (22nd January 2019) - Candoni, A.; Klimko, N.; Busca, A.; Di Blasi, R.; Shadrivova, O.; Cesaro, S.; Zannier, M. E.; Verga, L.; Forghieri, F.; Calore, E.; Nadali, G.; Simonetti, E.; et al.
Summary: Invasive fungal infections (IFI) of the Central Nervous System (IFI‐CNS) and Paranasal Sinuses (IFI‐PS) are rare, life‐threatening infections in haematologic patients, and their management remains a challenge despite the availability of new diagnostic techniques and novel antifungal agents. In addition, analyses of large cohorts of patients focusing on these rare IFI are still lacking. Between January 2010 and December 2016, 89 consecutive cases of Proven (53) or Probable (36) IFI‐CNS (71/89) and IFI‐PS (18/89) were collected in 34 haematological centres. The median age was 40 years (range 5‐79); acute leukaemia was the most common underlying disease (69%) and 29% of cases received a previous allogeneic stem cell transplant. Aspergillus spp . were the most common pathogens (69%), followed by mucormycetes (22%), Cryptococcus spp . (4%) and Fusarium spp . (2%). The lung was the primary focus of fungal infection (48% of cases). The nervous system biopsy was performed in 10% of IFI‐CNS, and a sinus biopsy was performed in 56% of IFI‐PS ( P  = 0.03). The Galactomannan test on cerebrospinal fluid has been performed in 42% of IFI‐CNS (30/71), and it was positive in 67%. Eighty‐four pts received a first‐line antifungal therapy with Amphotericine B in 58% of cases, Voriconazole in 31% and both in 11%. Moreover, 58% of patients received 2 or more lines of therapy and 38% were treated with a combination of 2 or more antifungal drugs. The median duration of antifungal therapy was 60 days (range 5‐835). A surgical intervention was performed in 26% of cases but only 10% of IFI‐CNS underwent neurosurgical intervention. The overall response rate to antifungal therapy (complete or partial response) was 57%, and 1‐year overall survival was 32% without significant differences between IFI‐CNS and IFI‐PS. The overall mortality was 69% but the IFI attributable mortality was 33%. Mortality of IFI‐CNS/PS remains high but, compared to previous historical data, it seems to be reduced probably due to the availability of newer antifungal drugs. The results arising from this large contemporary cohort of cases may allow a more effective diagnostic and therapeutic management of these very rare IFI complications in haematologic patients.